Kratos & krater : reconstructing an Athenian protohistory - Bohen, Barbara (Archaeopress archaeology., 2017)
Athenian governance and culture are reconstructed from the Bronze Age into the historical era based on traditions, archaeological contexts and remains, foremost the formal commensal and libation krater. Incorporated into this work is a monograph on the Athenian formal krater used by these primarily Neleid aristocratic houses in assembly and ritual.